2010
DOI: 10.1002/jca.20246
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting stem cell mobilization for autologous hematopoietic stem cell transplantation

Abstract: High-dose chemotherapy with autologous stem cell transplantation (ASCT) is curative treatment in various hematologic malignancies. Mobilization and collection of peripheral blood stem cell is the essential part of ASCT. The aim of this study was to evaluate the effectiveness of various mobilization regimens, determine the risk factors associated with mobilization failure (MF). We also investigated whether iron overload, which has an adverse impact on various aspects of HSCT including overall survival had any i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 29 publications
(43 reference statements)
0
43
0
Order By: Relevance
“…Several studies carried out to investigate this question showed that the diagnosis of lymphoma, [14][15][16][17][18][19] thrombocytopenia, 14,[20][21][22][23] older age [18][19][20][21][23][24][25] and polytreatment 14,16,19,25,26 , among other factors, emerged as the main potential factors for the prediction of poor recruitment of hematopoietic stem cells.…”
Section: Predictive Factors Of Poor Mobilizationmentioning
confidence: 99%
“…Several studies carried out to investigate this question showed that the diagnosis of lymphoma, [14][15][16][17][18][19] thrombocytopenia, 14,[20][21][22][23] older age [18][19][20][21][23][24][25] and polytreatment 14,16,19,25,26 , among other factors, emerged as the main potential factors for the prediction of poor recruitment of hematopoietic stem cells.…”
Section: Predictive Factors Of Poor Mobilizationmentioning
confidence: 99%
“…(8)(9)(10)(11)(12)(13). Ozkurt et al showed that poor mobilization frequency was higher in lymphoma patients (14). In our previous study, we have identified a diagnosis of lymphoma was a risk (odds ratio [OR] = 6.02, p = 0.001) factor (15).…”
Section: Introductionmentioning
confidence: 77%
“…The patients were treated with chemotherapy with (14 patients) or without (43 patients) radiotherapy. The median number of the chemotherapy cycles is 9 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the median of the number of the chemotherapy regimens is 2 (range 1-5). The number of the patients who were treated with rituximab was 27.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies describe that mobilization failure is more common in patients with thrombocytopenia, neutropenia, anemia, leukopenia. 5,9,10 …”
Section: Discussionmentioning
confidence: 99%